Irigasi dan Pendidikan Politik Etis di Kota Metro - Kurniawan, Adi; Prameswari, Anindya; Ekwandari, Yustina Sri (The Indonesian Journal of Social Studies, 2022)
In this study, the research focuses on the relics in the city of Metro during the application of ethical politics in the colonial era and its influence in the present. The implementation of ethical politics in Metro City has been started since 1905. By equalizing all Javanese people towards less densely populated areas, one of which is Lampung Province. In particular, Metro City, which was supported by a speech from Queen Wilhelmina, who declared a new policy to be implemented in the jurisdiction or area of application. With the existence of this new policy, namely the Application of Ethical Politics, known as the slogan of "education, irrigation, and emigration", which is commonly known as the van Deventer Trilogy or Trias Ethics. Despite wanting to present the population here, the colonial government supported the capitalists and industrialists and left the natives independent. The colonial government irrigated the areas of privately owned plantations, and built educational institutions by classifying them into aristocrats and civilians. Inequality occurs in all aspects of indigenous people's lives. However, unlike the success achieved due to the implementation of ethics in Metro City, it can be seen that the irrigation system and education system can run well. Thus, Metro City can provide an overview of the legacy policies both from its education system and its irrigation system which has been running well until now.